Tekno-Ekonomi Sistem Membran Terintegrasi untuk Pengolahan Air Baku Campuran Air Payau dan Efluen STP - I Nyoman Widiasa; Asteria A. Susanto (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Recently, portable water supply is one of crucial problems in the world, including Indonesia because water is not a cheap natural resource. Saline waters such as brackish water, seawater, and wastewater have been used as alternative raw water sources to fulfil domestic and idustrial water demands. Water price higher than IDR 15,000 clearly indicate that treatment of brackish water and/or wastewater reuse is effective from cost point of view. This work is aimed to perform in-situ pilot test by involving user and investor directly. Moreover, technical and cost are analysed based on a case study, i.e. average production of 220,000 m3/year; water price of IDR 14,500/m3 that increase IDR 2,000 every two years. This water treatment plant requires capital cost of 3.5 billions rupiahs. The capital comes from bank loan with interest of 13% per annual. It is found that with contract duration of 10 years, net present value (NPV) is positive so that this investment is feasible.